Pemanfaatan Ruang Publik sebagai Bentuk Perlawanan: Studi Kasus Kaltim Kamisan Melawan Pembatasan Demokrasi - M. Jamil Nur; Niken Nurmiyati; Alberto Noviano Patty; Paisal Akbar (Universitas Muhammadiyah Makassar, 2026)
The urgency of this research departs from the declining quality of democracy in Indonesia, marked by restrictions on civil liberties, restrictive regulations, and repressive practices in public spaces that remain insufficiently addressed. This study aims to analyze the utilization of public space as a form of civil society resistance through Aksi Kamisan East Kalimantan in responding to democratic restrictions. The method used is a qualitative case study by utilizing observation, in-depth interviews, and literature study, with data analyzed through a phenomenological approach. The results show that Aksi Kamisan East Kalimantan utilizes public space as a strategic arena to voice human rights, environmental, and social justice issues while resisting state domination, revealing patterns of restriction such as intervention, administrative pressure, and intimidation, alongside the emergence of counter-hegemonic discourse through peaceful and symbolic actions. These findings imply that public space functions not only as a site of resistance but also as a medium for democratic learning. The novelty lies in examining public space as a counter-hegemonic arena in a local context. This research contributes theoretically and practically by strengthening the understanding of participatory democracy and the importance of inclusive public spaces.